PENGARUH KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP KINERJA MELALUI KEPUASAN KERJA PADA ANGGOTA DIREKTORAT RESERSE NARKOBA POLDA KALTIM - Tutik Yuliani; Misna Ariani; Tamzil Yusuf; Didik Hadiyatno; Imam Arywibowo; Alviana Ajeng Hardianto (Program Studi Manajemen Fakultas Ekonomi Universitas Balikpapan, 2023)
This study aims to analyze the effect of leadership style and work discipline on the performance of members of the East Kalimantan Police's drug investigation directorate, both directly and indirectly. This type of research is quantitative. The software used in this research is Smart PLS. The subjects in this study were members of the East Kalimantan Police's drug investigation directorate, totaling 46 respondents. Resultsl Research shows that leadership influences job satisfaction. Work discipline affects job satisfaction. Leadership affects performance. Work discipline affects performance. Job satisfaction affects performance. Leadership influences performance through job satisfaction. Work discipline affects performance through job satisfaction.